The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3329/ijarit.v11i1.54472
|View full text |Cite
|
Sign up to set email alerts
|

Problem confrontation of sugarcane farmers in Natore district of Bangladesh

Abstract: The present study was conducted to explore the problems of sugarcane farmers in the selected areas of Natore district in Bangladesh. A total of 100 farmers were selected from Lalpur upazila of Natore district by using a simple random sampling technique. Data were collected through individual interviews during October to November, 2019 by using a structured interview schedule. Both descriptive and inferential statistics were used to analyze data. The majority of the sugarcane farmers (80%) had medium problems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This might imply that farmers' exposure to extension media contact provides an opportunity to get new techniques and knowledge of farming, which can significantly affect their training needs on tilapia fish culture. Extension media concept in terms of interpersonal and face to face forms of communication renders good sources of information for managing diversified farm activities effectively (Odini, 2014;Hoque et al, 2021). The finding is consistent with the results found by Sarker (2004) and Hossen (2016) in their study.…”
Section: Extension Media Contactsupporting
confidence: 85%
“…This might imply that farmers' exposure to extension media contact provides an opportunity to get new techniques and knowledge of farming, which can significantly affect their training needs on tilapia fish culture. Extension media concept in terms of interpersonal and face to face forms of communication renders good sources of information for managing diversified farm activities effectively (Odini, 2014;Hoque et al, 2021). The finding is consistent with the results found by Sarker (2004) and Hossen (2016) in their study.…”
Section: Extension Media Contactsupporting
confidence: 85%
“…Thus, farmers with greater communication exposure are more knowledgeable about using artificial feed in catfish culture than farmers with less or no exposure to communication. This is due to the fact that farmers with greater communication exposure have more options to contact various information sources for efficiently managing a variety of farm activities (Odini, 2014;Hoque et al, 2021) [36,26] . This finding is similar with a number of other studies that reported farmers having more commuination exposure usually plays a positive role in gaining knowldge Ali (2012) [1] , Farhad (2003) [22] , Sarker (2004) [43] and Hossen (2016) [30] .…”
Section: Relationship Between the Selected Characteristics Of The Fis...mentioning
confidence: 99%
“…Means of the variables x and y, respectively. Finally, the major 14 problems of LEAFs were measured by using a 4-point rating scale (Hoque et al, 2021). The respondents were asked to rate each problem as high, medium, low and not at all, with corresponding score of 3, 2, 1 and 0, respectively.…”
Section: Pearson's Product-moment Correlation Coefficientmentioning
confidence: 99%